ANALYSIS OF THE PHYSICAL AND MECHANICAL PROPERTIES OF FABRICS WOVEN WITH PLAIN AND REP WEAVES (E Global Congress, 2025)
The physical and mechanical properties of the fabric samples obtained from the enterprise and the proposed ones were analyzed based on GOST 31307-2005 and GOST 3816-81 (ISO 811-81) standards.For this purpose, fabric samples woven in plain and reps weaves were taken from the WALTEX pneumatic weaving machine available at the weaving department of Home Textile NT Holding LLC, and experiments were conducted.